Electrically conducting sandwich cylinder with a planar lattice core under prescribed eigenstrain and magnetic field. (1st October 2016) - Akbarzadeh, A.H.; Fu, J.W.; Liu, L.; Chen, Z.T.; Pasini, D.
Abstract: The eigenstrain theory is widely used to study inelastic responses of several classes of materials subjected to phase transformation, thermal expansion, and other multiphysics excitations. In this paper, we focus on electrically conducting cellular solids and examine their magnetoelastic responses when used as a core of a sandwich cylinder subjected to an eigenstrain and an external magnetic field. The cylinder comprises layers of either solid or cellular material and undergoes either plane strain or plane stress conditions in both time-harmonic and transient states. We use direct homogenization techniques (standard mechanics and micromechanical models) along with Bessel, Struve, and Lommel functions to study the roles that cell topology, relative density, eigenstrain, and bonding interface play on the magnetoelastic responses of the sandwich cylinder. The results show that relative density, cell topology, and magnetic field are the factors that most contribute to control the sandwich response. We also show that a careful tailoring of relative density and cell topology can lead to the simultaneous weight and overall stress reduction with improved natural frequency.